Color contrast processing in human striate cortex. - Kentridge, R; Heywood, C; Weiskrantz, L (2007)
Color constancy refers to the unchanging nature of the perceived color of an object despite considerable variation in the wavelength composition of the light illuminating it. The color contrasts between objects and their backgrounds play a crucial role in color constancy. We tested a patient whose right striate cortex had been removed and demonstrated that he made no use of color contrast in judging color appearance but instead made judgments based simply on wavelength comparison. This was shown by presenting pairs of colored stimuli against a background color that gradually changed across space. When presented with such displays, both normal observers and those with cerebral achromatopsia (cortical color blindness) judge the color appearance of such stimuli on the basis of the chromatic contrast the stimuli make against their background rather than on the physical wavelengths of the light emitted from them. However, our patient made no such use of color contrast but, instead, made color discriminations simply on the basis of wavelength composition. This is consistent with recent findings from monkey electrophysiology that identify cells in early cortical visual areas that signal local contrast and so contribute to the likely mechanism for achieving color constancy.